Next generation non-tariff measures: Emerging data policies and barriers to digital trade - Gloria O. Pasadilla; Yann Duval; Witada Anukoonwattaka (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
Trade used to be about goods crossing borders and the instrument of protection was mostly through tariffs. Then there was greater recognition of trade in services, now exceeding the share of goods in global trade. Because of services, the focus of trade protection shifted more towards "behind the border barriers" or domestic regulations that can obstruct services trade. More recently, the flows of goods and services are eclipsed yet again by data flows whose contribution to the economy is projected to reach 11 trillion USD by 2025. In the digital era, a new set of non-tariff measures - mostly related to data - have thus emerged. The paper seeks to understand the role of data in business and trade, the nature of some data flows restrictions and other digital trade barriers, and potential impact of data regulations.
Keywords: 330; Data Regulations; Digital Trade; Digital Trade Barriers; Non-tariff measures; NTMs